2021
DOI: 10.22456/1807-9806.108406
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting P-T conditions of Oriental Terrane and Central Superterrane (Ribeira Belt), NW of Rio de Janeiro state, Brazil

Abstract: Neoproterozoic-Cambrian rocks from the Oriental Terrane and the Central Superterrane of the Ribeira Belt occur in northwest of Rio de Janeiro state. This paper presents new data on field research, petrology, mineral chemistry and conventional geothermobarometry, fundamental to understanding the geology of the region. The metabasic rocks from the Cambuci Domain are associated with the Central Superterrane retroarc basin and record two metamorphic events: M 0 (before the formation of the main foliation, under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As evidenced by the morphology of the zircon grains and high Th/U ratios, the high metamorphic grade of the rocks is also evidenced by mineral peak metamorphic associations typical of the granulite facies (with orthopyroxene + clinopyroxene + plagioclase) in all study samples. The Neoproterozoic granulite metamorphism is common in the entire JFC (Duarte et al 1997, Heilbron et al 1998, Medeiros Júnior et al 2017) and is also observed in nearby units, such as the paragneisses from the Raposos and Bom Jesus do Itabapoana groups and in the orthogneisses from the Neoproterozoic Serra da Bolivia/Rio Doce magmatic arc (Karniol et al 2009, Santos et al 2011, Gouvêa et al 2020, Marques et al 2021). In addition, the observation of hornblende and biotite partially substituting orthopyroxene and clinopyroxene in some samples suggests retrometamorphism in conditions of upper amphibolite facies, also in agreement with regional works (Santos et al 2011, Ferreira et al 2020, Marques et al 2021.…”
Section: Neoproterozoic Metamorphic Overprintmentioning
confidence: 97%
“…As evidenced by the morphology of the zircon grains and high Th/U ratios, the high metamorphic grade of the rocks is also evidenced by mineral peak metamorphic associations typical of the granulite facies (with orthopyroxene + clinopyroxene + plagioclase) in all study samples. The Neoproterozoic granulite metamorphism is common in the entire JFC (Duarte et al 1997, Heilbron et al 1998, Medeiros Júnior et al 2017) and is also observed in nearby units, such as the paragneisses from the Raposos and Bom Jesus do Itabapoana groups and in the orthogneisses from the Neoproterozoic Serra da Bolivia/Rio Doce magmatic arc (Karniol et al 2009, Santos et al 2011, Gouvêa et al 2020, Marques et al 2021). In addition, the observation of hornblende and biotite partially substituting orthopyroxene and clinopyroxene in some samples suggests retrometamorphism in conditions of upper amphibolite facies, also in agreement with regional works (Santos et al 2011, Ferreira et al 2020, Marques et al 2021.…”
Section: Neoproterozoic Metamorphic Overprintmentioning
confidence: 97%